Struktur naratif cerpen Berguru Kepada Ibu dalam buku Sawang Sinawang: Prespektif naratologi Gerard Genette - Basri, Mochammad Faizal (Maliki Interdisciplinary Journal, 2024)
This study aims to describe the narrative structure of the short story Berguru on mothers in Sawang Sinawang’s book. The researcher finds five narrative structures with Gerard Genette’s narratology theory. First, the Narrative Order (order) as a story in parallel short stories does not precede or end or is called an acronym. Second, Narrative Duration uses two patterns, namely Pause and Scene, even though the scene is more dominant. The three Narrative Frequencies found repetition of the same story with action. The technique used is Anaphoric Representation. Fourth, the Narrative Mode (mood) with the Internal Focalization technique where the narrator has parallels with the main character, only saying what the character knows. The five Narrative Voices (voice) use the Simultaneous technique, that is, the narrator tells about events and actions that are happening in the present, where the background of a story tells of a time in the short story.